Short-term effects of etifoxine on human gut microbiome in healthy men - Manook, André; Baghai, Thomas C.; Riebel, Marco; Nothdurfter, Caroline; Schwarzbach, Jens Volkmar; Gessner, André; Rupprecht, Rainer; Hiergeist, Andreas (Frontiers in Neuroscience, 2023)
Neurosteroids have recently gained in interest as a treatment strategy for affective disorders. Etifoxine is known for its dual mode of action, one of which is to stimulate endogenous neurosteroid synthesis. The gut microbiome has been studied in affective disorders, but it has not been investigated in the context of human etifoxine or neurosteroid interventions. Therefore, we performed a crossover study with 36 healthy male volunteers who received etifoxine versus alprazolam and placebo in a balanced Williams design. Participants were randomized into six sequences and went through three five-day treatments followed by wash-out phases of nine days. Bacterial compositions in stool samples were determined by high-throughput 16S rRNA amplicon sequencing. Gut microbiome analyses revealed no relevant effects between treatments with respect to alpha and beta diversity. Differential abundance analyses yielded etifoxine treatment as the only effect related to changes in microbial features with reductions of Faecalibacterium duncaniae, Roseburia hominis and Lactobacillus rogosae (i.e. Bacteroides galacturonicus). Here we report on the first human investigation of the gut microbiome with short-term etifoxine intervention. Differences in diversity and compositional structure of the microbiome were more likely due to between-subject effects rather than medication. However, five-day treatment with etifoxine reduced the abundance of a few bacterial species. These species are currently seen as beneficial components of a healthy intestinal microbiome. This reduction in abundances may be related to elevated endogenous neurosteroids.